The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0969733020921493
|View full text |Cite
|
Sign up to set email alerts
|

Relational influences on experiences with assisted dying: A scoping review

Abstract: Background: Family members and healthcare providers play an integral role in a person’s assisted dying journey. Their own needs during the assisted dying journey are often, however, unrecognized and underrepresented in policies and guidelines. Circumstances under which people choose assisted dying, and relational contexts such as the sociopolitical environment, may influence the experiences of family members and healthcare providers. Ethical considerations: Ethics approval was not required to conduct this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…This study highlights how healthcare providers’ moral agency, including their decisions to participate in MAiD using written waiver of final consent, is influenced by their personal values and experiences, power dynamics and relationality [ 25 ]. Similarly, previous studies have reported that socio-political, ethical and legal ramifications and lack of support influenced healthcare providers’ decisions to participate in MAiD [ 8 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This study highlights how healthcare providers’ moral agency, including their decisions to participate in MAiD using written waiver of final consent, is influenced by their personal values and experiences, power dynamics and relationality [ 25 ]. Similarly, previous studies have reported that socio-political, ethical and legal ramifications and lack of support influenced healthcare providers’ decisions to participate in MAiD [ 8 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 82%
“…An increase in workload to address the potential legal and professional liabilities is predicted. The potential for burden is high due to unclear eligibility criteria and safeguards as well as socio-political constraints such as lack of resources, time, remuneration and support as has been noted in other studies [ 8 , 13 , 32 , 38 , 39 ]. In addition, patients and family members may have unrealistic expectations about access to MAiD and the role of the healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, additional data are needed to evaluate and improve the service (eg, feedback from providers, patients and families, analyses of the process including its policy, functionality, efficiency, effectiveness, impacts and sustainability and so on). 24 Canadian providers and health systems are actively working to improve the MAID experiences of patients, families and professionals, [25][26][27][28] but it remains challenging to improve its implementation without knowing what the process looks like. Studies describing professional roles, expectations and knowledge gaps 9 15 29-32 or how MAID was implemented 4 5 9 33-37 provide few details about the process itself (eg, how work is coordinated between professionals, which professional(s) do which activities and when and so on).…”
Section: Introductionmentioning
confidence: 99%